The Effects of Well-Being and Mindfulness on Teacher Enthusiasm - Alsaleem, Alaa Abdullah; Abusamhadaneh, Karim Ahmad (Journal of Posthumanism, 2025)
This study investigates the impact of well-being and mindfulness on teacher motivation, exploring how these factors affect emotion regulation, stress levels, job satisfaction, and classroom dynamics. The study synthesises existing literature and uses quantitative methods to analyse data from 100 teachers with different educational levels. The study results show that both happiness and mindfulness can significantly improve teachers’ motivation, and mindfulness moderates the relationship between happiness and motivation to a certain extent. The study concludes with practical recommendations for integrating wellness and mindfulness practices into teacher professional development programs to create more positive and effective teaching environments.